Comparative Environmental Impacts and Development Benefits of Coastal Aquaculture in Three Tropical Countries: Madagascar, Tanzania and Indonesia - Andreas Kunzmann; Gildas Todinanahary; Flower E. Msuya; Yustian Alfiansah (Tropical Life Sciences Research, 2023)
Aquaculture is still in early development in Madagascar and Tanzania, while in Indonesia, aquaculture has a long history. In Madagascar, villagers are farming seaweed and sea cucumbers, as part of small-scale community-based aquaculture (CBA). They followed a contractual model between a private farming company and farmers. Local non-governmental organizations (NGOs) and public institutions in Madagascar jointly strive to reverse the trend of ongoing anthropogenic coastal degradation. In Tanzania, the cultivation of red seaweeds has been established for over 30 years, with declining production attributed to climate change. While shrimp farming still involves, to some extent, clearing of mangroves in Tanzania, seaweed culture has only mild impact on coastal ecosystems. Farming areas provide shelter and habitat for juvenile fish, crabs and other organisms. Therefore, NGOs ask for support to improve culture methods. Various problems and shortcomings in Indonesia have been clearly identified, including issues related to new aquaculture areas, pollutants, emerging diseases, insufficient broodstock and fry supply, as well as a lack of technology and manpower. To address these challenges and ensure the growth of aquaculture production, the government has implemented national policies and established training and broodstock centers throughout the country. In Madagascar, the CBA programme stands out as a success story and can serve as a template for other coastal regions and countries. In Tanzania, adoption of the CBA model for co-culture could be the future. In Indonesia, due to a very long coastlines and complicated legislation, IMTA seems to be particularly suitable, as successfully tested in model regions.